The prevalence of the known risk factors for teenage pregnancy amongst female teenage learners in Mount Ayliff, Eastern Cape, South Africa - Okafor, Sylvester (Stellenbosch : Stellenbosch University, 2016)
Thesis (MMed)--Stellenbosch University, 2010.